Receipt of substance-use services by caregivers involved in the child-welfare system. (May 2020) - Cheng, Tyrone C.; Lo, Celia C.
Highlights: Receipt of substance use services related to inclusion of the services in case plan. Such services receipt related to nonmedical medicine use and need of other services. Caregivers refused services were not likely to receive substance use services. Receipt of such services was not likely when children stayed in parent's home. Caregivers substantiated for neglect were likely to receive such services. Abstract: The present study of children's caregivers involved in child welfare examined the factors associated with their receiving services for substance use. Our sample of 1445 such caregivers for whom maltreatment had been substantiated was extracted from a national data set. The results of generalized estimating equations showed that caregivers' receipt of substance use services was associated positively with nonmedical use of medication; with number of services needed; and with inclusion of substance use services in the case plan. Additionally, caregivers' receipt of substance use services was associated negatively with lack of access to such services; with refusal of services; with physical and with sexual maltreatment; and with child's placement in parent's home. No significant associations appear to link receipt of substance use services to gender, race/ethnicity, education, family income, health insurance status, or caseworker–caregiver engagement. The findings imply the importance of identifying need for substance use services among caregivers involved in child welfare and mandating services for them. As well, they imply the need for child welfare professionals to collaborate and coordinate with other professionals.